Rancang Bangun Prototipe Aplikasi Konsultasi Menu Makanan Berbasis Mobile Bagi Penderita Penyakit Diabetes Menggunakan Metode Harris Benedict - Gede Bayu Eka Bhuana; Agi Putra Kharisma; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Sample Registration The 2014 survey said that diabetes was the third killer disease in Indonesia. Where according to Prof. Sid reporter, the risk of diabetes increases 30 percent every year it is recommended that we check blood sugar once a year. But the cost of paying a food consultant for diabetics has become one of our difficulties in managing our own diet. The price of the services of food consultants has reached more than one million meetings. By these factors also the interviews that I have done with graduates - new graduates of nutrition experts about their shortcomings will patients the authors are motivated to make a prototype based mobile application by utilizing Harris Benedict method that can help nutritionists and patients. This application prototype was built using Android. In the process of determining calories, this application utilizes the Harris Benedict method to determine calorie requirements for diabetics. Later, an application will be produced that can help diabetics to find food menu consultants also help nutritionists to get patients